A Legal Framework for Social Forestry Management that Provides Access Rights to Communities in Forest Resource Utilization - EDRA SATMAIDI EDRA SATMAIDI (Institut Agama Islam Negeri Curup, 2025)
This study aims to explore and establish a national legal framework that provides a legal basis for community access rights in the utilization of forest resources. This study emphasises the importance of shifting the paradigm from entirely state-based forest management, to community-based forest management that will strengthen state forest management. This research uses normative legal research methods with qualitative juridical analysis of legal materials. The results show that there is a strong legal framework both at the level of the constitution, Constitutional Court decisions, and laws and regulations, up to the level of technical regulations in the Minister of Environment and Forestry Regulation. Social Forestry policy and its implementation can provide legal certainty and justice for community access rights in forest resource utilization. However, Social Forestry in its implementation also contains a number of challenges that need to be addressed.